Effect of Debt Restructuring Through Debt To Equity Swap Policy Towards Financial Performance of PT. XYZ (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2020)
This study aims to determine the effect of debt restructuring through the debt to equity swap policy on the financial performance of PT XYZ. In this study the data used were from 2012 to 2018 ago. In this study time interest earnings are used as control variables, while the main variables are profitability ratios, activity ratios and liquidity ratios. The method of analysis is done by using multiple regression analysis. Based on the results of hypothesis testing, it was found that debt restructuring as measured by the debt to equity ratio has a significant effect on profitability and activity ratios, while debt restructuring has no effect on PT XYZ's corporate liquidity.